2021
DOI: 10.3892/etm.2021.10379
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA PCAT6 regulates bladder cancer progression via the microRNA‑143‑3p/PDIA6 axis

Abstract: Although long non-coding (lnc)RNAs have been reported to be involved in the pathological development of bladder cancer, the functions of lncRNA prostate cancer-associated transcript 6 (PCAT6) and its underlying mechanism of action in bladder cancer remain unknown. The present study aimed to investigate the effect of PCAT6 in bladder cancer progression and explore its potential application as a novel treatment target. The expression of PCAT6 and miR-143-3p in bladder cancer tissues, adjacent normal tissues and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Cheng once demonstrated that PDIA6 downregulation inhibited BC cell proliferation and invasion via the Wnt/β-catenin signaling pathway ( Cheng et al, 2017 ). Meanwhile, Zhang discovered that lncRNA PCAT6 could regulate BC progression via the microRNA-143-3p/PDIA6 axis ( Zhang et al, 2021d ). Furthermore, POP4, PREB, SRPRB, TATDN2, YIF1A, and ZBTB17 were seldom studied in BC and perhaps researchers need to pay more attention to them in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Cheng once demonstrated that PDIA6 downregulation inhibited BC cell proliferation and invasion via the Wnt/β-catenin signaling pathway ( Cheng et al, 2017 ). Meanwhile, Zhang discovered that lncRNA PCAT6 could regulate BC progression via the microRNA-143-3p/PDIA6 axis ( Zhang et al, 2021d ). Furthermore, POP4, PREB, SRPRB, TATDN2, YIF1A, and ZBTB17 were seldom studied in BC and perhaps researchers need to pay more attention to them in the future.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of abnormally expressed lncRNAs have been detected in bladder cancer that affect the occurrence, proliferation and migration of bladder cancer cells. For example, Zhang et al reported that the lncRNA PCAT6 regulates the proliferation and migration of bladder cancer through the miR-143-3p/PDIA6 axis (Zhang et al, 2021). In addition, Chen et al found that the lncRNA LNC-LBCS inhibits the self-renewal and chemotherapy resistance of bladder cancer stem cells through the epigenetic silencing of SOX2 (Chen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of PCAT6 is found to be aberrantly elevated in various human tumor tissues and cell lines compared with matched normal ones, including bladder cancer (BC) [ 21 , 24 , 25 ], breast cancer (BrCa) [ 26 , 27 ], cervical cancer (CC) [ 28 , 29 ], colorectal cancer (CRC) [ 30 , 31 ], gastrointestinal stromal tumor (GIST) [ 32 ], gastric cancer (GC) [ 33 , 34 ], glioblastoma (GBM) [ 35 ], hepatocellular carcinoma (HCC) [ 36 , 37 , 38 ], lung cancer (LC) [ 20 , 39 , 40 , 41 , 42 , 43 ], osteosarcoma (Osa) [ 44 , 45 , 46 ], ovarian cancer (OvCa) [ 47 , 48 ], cholangiocarcinoma (CCA) [ 49 ], pituitary adenoma (PA) [ 50 ], pancreatic ductal adenocarcinoma (PDAC) [ 51 ], and prostate cancer (PCa) [ 52 , 53 ]. In subsequent experiments on the biological functions of tumor cells, it has been revealed that a high level of PCAT6 has strong cancer-promoting effects, mainly including the promotion of cell proliferation, enhancement of migration, invasion and EMT process, as well as the inhibition of cell apoptosis.…”
Section: Expression and Subcellular Localization Of Pcat6mentioning
confidence: 99%
“…LncRNAs play diverse functions depending on different subcellular or extracellular compartmental localizations. Most studies indicate that PCAT6 is primarily located in the cytoplasm of BC [ 25 ], GIST [ 32 ], GBM [ 35 ], Osa [ 44 , 45 ], PA [ 50 ], and Pca [ 52 ] cells. Cytoplasmic lncRNAs regulate genes at the translational and post-transcriptional levels, such as interaction with cytoplasmic proteins [ 58 ], and interaction with microRNAs to regulate downstream mRNA levels [ 59 , 60 , 61 , 62 , 63 ].…”
Section: Expression and Subcellular Localization Of Pcat6mentioning
confidence: 99%
See 1 more Smart Citation